Effects of Knowledge, Feedback and Equipment Provision on Practices and Efficiency of Environmental Cleaning Among Personnel in General Hospital - Nuankum , Tussanee; Unahalekhaka , Akeau; Chitreecheur , Jittaporn (Nursing Journal CMU, 2021)
Cleaning the hospital environment is an important activity in preventing microorganism transmission within the hospital. This quasi-experimental research, one group pre and post-test design, aimed to determine the effects of educating, giving feedback and providing support for cleaning equipment on the cleaning practices and the efficiency of environmental cleaning of 16 nursing assistants and patient care personnel working in a general hospital. The study was conducted from November 2015 to January 2016. Study activities included educating the sample, demonstration and return demonstration, provision of a hospital environmental cleaning manual, giving feedback and providing support for environmental cleaning equipment. Sample general information was collected using a self-administered questionnaire. Researcher observed cleaning practices and assessed the efficiency of cleaning using a fluorescent dye. Data were analyzed using descriptive statistics and Chi-Square Test. Participants were between 20-54 years old with a mean age of 28.75 years and mainly female (93.75%) and most were high school graduates (68.75%). Most (87.5%) had received training on environmental cleaning and had worked at the hospital from two months to fourteen years with a mean working time of 3.96 years. The study results revealed that after the intervention, overall correct cleaning practices within the sample increased significantly from 41.30% to 82.83% (p < .001). The overall efficiency of cleaning increased significantly from 32.34% to 75.18% (p < .001). The study results show that promoting practices using a multimodal intervention can increase correct practices and the efficiency of environmental cleaning. Educating, giving feedback and adequate cleaning equipment should be provided for responsible personnel.